2009
DOI: 10.1002/per.710
|View full text |Cite
|
Sign up to set email alerts
|

Examining dispositional and situational effects on outgroup attitudes

Abstract: . We wish to thank Rupert Brown for reading over an earlier version and for providing helpful comments. In Press, European Journal of PersonalityExamining dispositional and situational effects on outgroup attitudes 1 Abstract Two research lines have dominated the quest for the antecedents of outgroup attitudes. Whereas the first has viewed outgroup attitudes as a result of individual differences, the second stressed the importance of the intergroup situation. In order to investigate the interplay of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Halabi et al (2008) found that high SDOs offered less help to a hypothetical outgroup member under conditions of status threat. However, others report nonsignificant SDO Â experimental threat interactions (Cohrs & Asbrock, 2009;Meeus, Duriez, Vanbeselaere, Phalet, & Kuppens, 2009). These inconsistent findings pertaining to SDO Â threat effects within experimental contexts heightens the need for additional experimental research.…”
Section: Social Dominance-based Reactions To Intergroup Threatmentioning
confidence: 99%
“…Halabi et al (2008) found that high SDOs offered less help to a hypothetical outgroup member under conditions of status threat. However, others report nonsignificant SDO Â experimental threat interactions (Cohrs & Asbrock, 2009;Meeus, Duriez, Vanbeselaere, Phalet, & Kuppens, 2009). These inconsistent findings pertaining to SDO Â threat effects within experimental contexts heightens the need for additional experimental research.…”
Section: Social Dominance-based Reactions To Intergroup Threatmentioning
confidence: 99%
“…This hypothesis stems from research on the power motive (Winter, 1973), the power-as-control model (Fiske, 1993), and the approach-inhibition perspective (Keltner, Gruenfeld, & Anderson, 2003). Accordingly, chronic motives may affect implicit judgments (see Meeus, Duriez, Vanbeselaere, Phalet, & Kuppens, 2009;Pratto & Shih, 2000). Furthermore, power may increase automatic social cognition, and powerlessness may trigger controlled cognition (Keltner et al, 2003;see also Fiske, 1993;Guinote, 2007a).…”
Section: Why Does Perceiver Power Increase Implicit Prejudice?mentioning
confidence: 99%
“…; Meeus et al. ). In addition, in line with the idea that individuals who identify themselves strongly with their national in‐group start behaving in accordance with existing in‐group norms, longitudinal data collected among Dutch‐speaking Belgians in Flanders show that the relation between Flemish identification and out‐group derogation is mediated by the way in which people represent citizenship: the more Flemish people identify with the Flemish in‐group, the more ethnic their citizenship representation becomes, and as a result, the more negative their out‐group attitudes become (Meeus et al.…”
mentioning
confidence: 96%